The hydrogen-bonded dianion of vitamin K1 produced in aqueous–organic solutions exists in equilibrium with its hydrogen-bonded semiquinone anion radical - Lim, Zhen Hui (2013)
When the quinone, vitamin K1 (VK1), is electrochemically reduced in aqueous-acetonitrile solutions (CH3CN with 7.22 M H2O), it undergoes a two-electron reduction to form the dianion that is hydrogen-bonded with water [VK1(H2O)y2–]. EPR and voltammetry experiments have shown that the persistent existence of the semiquinone anion radical (also hydrogen-bonded with water) [VK1(H2O)x–•] in aqueous or organic–aqueous solutions is a result of VK1(H2O)y2– undergoing a net homogeneous electron transfer reaction (comproportionation) with VK1, and not via direct one-electron reduction of VK1. When 1 mM solutions of VK1 were electrochemically reduced by two electrons in aqueous-acetonitrile solutions, quantitative EPR experiments indicated that the amount of VK1(H2O)x–• produced was up to approximately 35% of all the reduced species. In situ electrochemical ATR-FTIR experiments on sequentially one- and two-electron bulk reduced solutions of VK1 (showing strong absorbances at 1664, 1598, and 1298 cm–1) in CH3CN containing <0.05 M H2O led to the detection of VK1–• with strong absorbances at 1710, 1703, 1593, 1559, 1492, and 1466 cm–1 and VK1(H2O)y2– with strong absorbances at 1372 and 1342 cm–1.